Zarządzanie płynnością grupy kapitałowej - Grabowska, Magdalena (Liquidity Management of Capital Group, 2007)
The globalization, becoming a worldwide process and most more quickly getting of almost all industries and economy sections, is possible thanks to the progressive concentration of capital. This appears in connections and mergers of economic subjects, leading to rise of great, national, and often supranational capital groups. In the face of such occurrence of the consolidation, observed also in Poland since 1990s, the essential meaning gathers the matter of the management with such composed subjects. The article concentrates on the aspect of the financial liquidity from the capital group point of view. A true success is not only to sell the commodity, but first of all to recover the cash termly of its pay, and then properly to bring it into cultivation. The article introduces the influence of rules of the accountancy, practical at the creation of consolidated finance statements for capital groups on their financial liquidity indicators. One turned also the attention to the efficiency of one of the tools offered by banks in the improvement of the financial liquidity of capital groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 115-124